Identidade em Diálogo: A identidade cultural do negro africano a partir de uma análise da convivência em um Instituto missionário católico pluricultural - Rufin, Waway Kimbanda (2007)
The major cultural changes that are emerging nowadays present a new identity and a sharp interrogation of its theories apart from social-relational tensions. In this respect, the object of this research presents a scientific theme in general for curiosity purposes. Brought to the camp of Religious Sciences, it aims at integrating the debate process about different dimensions of cultural pluralism and religious phenomenon of the contemporary society. The study base itself on a multi-cultural catholic religious group: The Comboni Missionary Institute. In its derivation, the thesis analizes the paradigm of the inter-cultural experience of Daniel Sorur Pharim Deng, of the Dinka African ethnic group, as an anthological illustration of cultural identity of a black man in the context of this multi-cultural catholic institution. In this context, the cultural identity of the black African must be understood in its inter-cultural relation, as collective and plural. Secondly, the thesis not only dares to discuss cultural identity and inter-cultural concepts pointing to its academic insufficiency and ambiguity in its ecclesial and neo-liberal use, but also aims at its living validity. Lastly, after reflecting about the fundamental conditions for this intercultural dialogue, the research proposes the inter-culturation paradigm that will get rid of the silence between ethnocentric acculturation and inculturation in the multi-cultural context. The inter-culturation helps to understand the theme in a concomitant, articulate and various ways, guarding all the lived experiences and expressions of the group s common ideal and at the same time safeguarding the wishes of all in the partiality of each cultural identity. In this way, the discussion of this thesis aims not only at operational horizon that is capable of facing the major challenges of cultures living together peacefully, but also a presentation of research sector in Religious Sciences, where many aspects are yet to be explored. Basically, this study operates in the interface between Anthropology, Religious Sciences and Theology and makes an appeal to discuss the problems raised by the religious phenomenon in the inter-cultural and inter-disciplinary horizon